Restricting Tobacco Retail Outlets Around Middle and High Schools as a Way to Reduce Tobacco Marketing Disparities: A Simulation Study. Issue 12 (23rd June 2022) - Obinwa, Udoka; Pasch, Keryn E; Jetelina, Katelyn K; Ranjit, Nalini; Perez, Adriana; Perry, Cheryl L; Harrell, Melissa
Abstract: Introduction: Communities with more people of color and economically disadvantaged residents are disproportionately exposed to tobacco marketing from tobacco companies. This study examined if banning tobacco retail outlets (TROs) within 1000 ft of schools would reduce these marketing disparities through a greater reduction in the amount of tobacco advertising around schools in these communities. Methods: Data from objectively audited advertisement data from 106 convenience stores and gas stations around 42 middle and high schools located in the four major metropolitan areas of Texas were linked with schools' enrollment data. ArcGIS (Aeronautical Reconnaissance Coverage Geographic Information System) was used to simulate a 1000-ft ban of tobacco sales around the schools. Independent sample T -tests and Mann–Whitney U tests were used to test mean differences where appropriate. Results: Schools with a higher enrollment of Hispanic/Latino (mean = 171.6, SD = 96.9) and economically disadvantaged students (mean = 168.9, SD = 102.3) were surrounded with significantly greater advertising at TROs than schools with lower enrollment of these groups (mean = 82.8, SD = 49.1 and mean = 89.2, SD = 50.6, respectively). A simulated 1000 ft ban of TROs around schools led to greater advertising reduction around schools with a higher enrollment of Hispanic/Latino students (13.3%–29.4% reductions) in comparison to schools with lower Hispanic/Latino student enrollment. However, the more economically disadvantaged schools had a smaller reduction in the number of advertisements (5.9%–21.9% reductions) in comparison to schools with less economically disadvantaged students. Conclusion: The implementation of a ban of tobacco sales at TROs within 1000 ft of schools is one policy approach to reduce youth exposure to tobacco marketing, particularly among students of color. Study Implication: Tobacco retail outlets (TROs) around schools with a higher enrollment of Hispanic/Latino and economically disadvantaged students had significantly more tobacco advertisements in comparison to schools with lower enrollment of these student groups. A simulated ban of TROs within 1000 ft of schools led to greater advertising reduction around schools with a higher enrollment of Hispanic/Latino students. For schools with more economically disadvantaged students, the ban led to a smaller reduction in advertisements in comparison to schools with less economically disadvantaged students. This proposed place-based strategy could be a successful means to reduce tobacco advertising and marketing disparity among communities of color.